Status Monitoring Set and Data Logger for 50 kVA 3-Phase Distribution Transformer - Wongta, Dumrongsak; Muangchuen , Satawat; Yodkad , Paitoon (RMUTL Engineering Journal, 2022)
A set of status monitoring and data logger for the use of distribution transformers was installed on a 3-phase transformer rated at 50 kVA. In the installation, current sensors and voltage sensors were used to measure values and send to the microcontroller board for processing and recording in the data logger. The purpose of this paper, in addition to studying the use of transformer in distribution of power to a load rated at no more than 80% of the transformer rating, is to implement a display for phase A, B and C load states. The status display used color lamps according to the specified conditions: green lamp (normal), yellow lamp (warning) and red lamp (overload). The results showed that the studied transformer provided a maximum power of 65% and the transformer still had 15% of the power to support the load. Moreover, for each phase of the operating load conditions, the lamps can display load balance values according to recorded data in the data logger.